Electrochemical Studies of Magnesium Coated with Modified Chitosan and Electrosprayed as an Anticorrosive Protection Method in Bone Repair - Ramírez-Reyes, Jose Luis; Gaytán-Macías, Deni Esperanza; Quintana-Camacho, Harlem; Galicia Aguilar, Gonzalo; González Mancera, Guillermina (Revista Mexicana de Ingenieria Biomedica, 2023)
Magnesium (Mg) is essential for the metabolic reactions of the human body and is known for its biocompatibility, its mechanical and physical properties are similar to human bone, which is why it is considered to have high potential in biomedical applications such as temporary and resorbable implants. Through surface modifications, the high tendency to corrosion of Mg could be controlled, such as biodegradable membranes that prevent the passage of chloride ions present in the human organism. To prepare the membrane, solutions of chitosan modified with gelatin and/or glutaraldehyde are used and by means of the electrospray method applied to protect the Mg. To simulate body fluid conditions a Kokubo saline solution (BFK) was prepared. The study focuses on evaluating the corrosion rate of Mg with a coating made of a chitosan electrosprayed membrane, applying electrochemical measurements of electrochemical impedance spectroscopy and linear polarization resistance. The key additive to improve the behavior of the membranes was observed with the use of gelatin, where the membrane with the best results lowing corrosion rates is the Mg CH+GE+GL system, which it was observed with very good physical integrity in the images of morphological analyzes of the surface after 30 days of exposure.